Factors influencing orthodontic treatment outcome in South East Wales and implications for service commissioning. (December 2019) - Quach, Stacey; Popat, Hashmat; Karki, Anup; Playle, Rebecca; Richmond, Stephen
Aim: To determine factors that may influence the outcome of orthodontic treatment undertaken in General Dental Services/Personal Dental Services in South East Wales. Design and setting: A retrospective study of a requested 20 consecutively treated cases (for the year 2014–2015) provided by 26 performers in South East Wales. Method: Performer and patient information was obtained by use of a questionnaire and FP17OW forms, respectively. A calibrated investigator recorded the Index of Orthodontic Treatment Need (IOTN), Peer Assessment Rating (PAR) and the Index of Complexity, Outcome and Need (ICON) on start- and end-study models for each case. Descriptive and regression analyses were undertaken to identify any predictive factors of a good treatment outcome. Results: Two respondents completed < 20 cases, so all of their cases were assessed. A total of 495 cases were assessed. The overall achieved mean end-PAR score of 5 is collectively a good occlusal outcome. Predictive factors of a good quality of occlusal outcome (end-PAR score being ⩽ 5) were: dual arch treatment; use of functional with fixed appliances; treatment undertaken in non-corporate practices; and treatment undertaken by registered specialists ( P < 0.001). Predictive factors for occlusal improvement (change in PAR score) were: IOTN aesthetic component (AC); IOTN dental health component (DHC) (1–3 or 4–5); and number of arches treated and malocclusion type ( P < 0.001). Conclusions: Dual arch fixed appliances undertaken by orthodontic specialists in non-corporate environments produced the highest quality orthodontic outcomes. Those who have the highest need for treatment according to IOTN DHC and AC benefit most in terms of improvement achieved in PAR score.